Analysis Of Camel Method As A Measurement Tool For Bank Rakyat Indonesia Agroniga Tbk Financial Performance In The Period 2015 - 2020 - Rismawati, Gita; Lestiyadi, Ayu Puspa (Fin Sinergy: Jurnal Manajemen Keuangan, 2024)
The purpose of conducting this study entitled "Analysis of the Camel Method as a Measuring Tool for Financial Performance of Bank Rakyat Indonesia Argoniaga Tbk for the 2015-2020" period is to find out or analyze financial performance using the CAMEL method at Bank BRI Agroniaga Tbk which is listed on the Indonesia Stock Exchange in 2015-2020, to see if Bank BRI Agroniaga Tbk. are in a healthy or unhealthy predicate. The type of research conducted by the author is descriptive with a quantitative approach. The population in this research is the Annual Financial Report of Bank BRI Agroniaga Tbk. The sample used in this research is the financial statements for the last 6 years of Bank BRI Agroniaga Tbk. Data collection techniques in this study are using literature studies, field studies and internet studies (secondary data). The data analysis technique used is to calculate the data that has been obtained and then first analyze it with financial ratios, then determine the final CAMEL value for each period by multiplying the credit value of each ratio with the CAMEL weight determined by BI. The ratios used include CAR (Capital aspect), NPL (Assets aspect), NPM (Management aspect), ROA and BOPO (Earning aspect), and LDR (Liquidity aspect). The results of this study show that the final value of the CAMEL aspect in 2015 was 96.02, in 2016 it was 95.03, in 2017 it was 94.87, in 2018 it was 92.05, then in 2019 it was 92.85 and in 2020 it was 84.69 all indicating that the CAMEL value was in the range 81 – 100 so that it can be stated that the financial performance of Bank BRI Agroniaga Tbk which is listed on the Indonesia Stock Exchange using the CAMEL method in 2015-2020 is in the HEALTHYpredicate/category.